2005
DOI: 10.1093/occmed/kqi107
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of spirometric abnormalities among silicotic patients in Hong Kong

Abstract: In an occupational compensation setting, disease indices and history of tuberculosis are independent predictors of both airflow obstruction and reduced vital capacity for silicotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…In the present study, a history of TB was also associated with COPD. Previous studies from Africa and Asia have consistently shown a positive association between pulmonary TB and airflow obstruction 28–34 . Results from the PLATINO study in Latin America showed that subjects with a history of TB were more than twice as likely to present with airflow obstruction than those without TB, even after adjustment for confounding by age, gender, smoking and environmental exposures.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, a history of TB was also associated with COPD. Previous studies from Africa and Asia have consistently shown a positive association between pulmonary TB and airflow obstruction 28–34 . Results from the PLATINO study in Latin America showed that subjects with a history of TB were more than twice as likely to present with airflow obstruction than those without TB, even after adjustment for confounding by age, gender, smoking and environmental exposures.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with previous pulmonary TB were more likely to suffer from acute exacerbation of COPD than those who did not have pulmonary TB (15). In silicosis patients, history of TB is an independent predictor of airflow obstruction (16). The bronchodilator response of patients with a tuberculous-destroyed lung is lower than that of patients with COPD (17).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is an important cause of morbidity and mortality among silicotic patients [5] and both smoking and tuberculosis are independently associated with lung function impairment [28]. Smoking cessation is, therefore, expected to have major impact on the quality of life for patients suffering from this largely irreversible disease.…”
Section: Discussionmentioning
confidence: 99%